Coral transplantation on a multilevel substrate of Artificial Patch Reefs: effect of fixing methods on the growth rate of two Acropora species - M Munasik; AGUS SABDONO; AZELIA N. ASSYFA; DIAH PERMATA WIJAYANTI; SUGIYANTO SUGIYANTO; IRWANI IRWANI; RUDHI PRIBADI (Society for Indonesian Biodiversity, 2020)
Abstract. Munasik, Sabdono A, Assyfa AN, Wijayanti DP, Sugiyanto, Irwani, Pribadi R. 2020. Coral transplantation on a multilevel substrate of Artificial Patch Reefs: effect of fixing methods on the growth rate of two Acropora species. Biodiversitas 21: 1816-1822. Branching Acropora is generally used in coral transplantation to rehabilitate coral reefs. However, these corals are sensitive to environmental changes. Artificial Patch Reef  (APR) is an artificial structure that provides a multilevel hard substrate. The purpose of the study was to investigate the effectiveness of the APR structure to facilitate the growth and survival of Acropora branching. Two species Acropora aspera and Acropora copiosa were transplanted vertically and horizontally on a modular concrete block in different levels of APR situated in the shallow reef of Panjang Island, Central Java. The results showed that the coral growth rate varied from 96.7 to 346.9 cm3/month, while survival ranged from 30 to 100% after 8 months. Lower survival rate mostly was found in the upper level of APR. The statistical analyses showed that the growth rate of A. copiosa fragment was significantly higher than that of A. aspera  (p<0.05). Moreover, there were also significant differences in the treatments of transplantation method  (p<0.05) to enhance coral growth. However, multilevel substrates were not significantly influenced by coral growth. This study suggested that A. copiosa which has high-level complexity in branching pattern will be selected to apply in shallow reef rehabilitation with transplanted vertically.